Have We Achieved Optimal Skin Color Matching in Partial Facial Transplantation? A Survey Study of the General Public and Medical Professionals. Issue 8 (November 2020) - Park, Jenn J.; Diep, Gustave K.; Alfonso, Allyson R.; Berman, Zoe P.; Hoffman, Alexandra F.; Mills, Emily C.; Wolfe, Erin M.; Felsenheld, Julia H.; Ramly, Elie P.; Rodriguez, Eduardo D.
Abstract : Background: Skin color matching is an essential factor in achieving optimal aesthetic outcome in partial facial transplantation. However, there is no published literature evaluating the success of color matching to date. Furthermore, a medical professional's perception of an optimal color match may not necessarily translate to that of the general public. The purpose of our study was to evaluate skin color matching between the donor allograft and recipient native tissue in partial facial transplantations to determine the level of success perceived by the general public and medical professionals. Methods: Published photographs of partial face transplant recipients were used to create a survey where recipient native and donor allograft skin samples were juxtaposed. Thirty-three members of the general public and 30 medical professionals were asked to rate skin color match on a scale from "excellent match" to "not a match." Results: Overall, 47% of given ratings were positive, indicating an "excellent" or "good match, " and 53% of ratings were negative, indicating a "poor match" or "lack of match" between the skin sample pairings shown. Of the 19 partial face transplant patients who were rated, 9 patients received >50% positive ratings, and 10 patients received <50% positive ratings. Medical professionals consistently gave more positive ratings, with statistically significant differences in 7 of the 19 rated patients ( P < 0.05). Conclusion: The results suggest that there is need for improvement in color matching in partial facial transplantation, and that the general public is more critical of skin color matching compared to medical professionals. Abstract : Supplemental Digital Content is available in the text